STRATEGI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL DALAM PELAYANAN KEPEMILIKAN AKTA KELAHIRAN BAGI ANAK-ANAK PANTI ASUHAN DI KOTA MAKASAR - Taufan Alwany (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2020)
This study aims to analyze the strategy of the Department of Population and Civil Registration in the ownership of birth certificate services for orphanage children in the city of Makassar. This study uses a qualitative method through a descriptive approach in researching and analyzing the data under study. The author uses data triangulation techniques in conducting research, data acquisition using observations or observations, interviews, and documentation, and using SWOT analysis to find the right strategy in the birth certificate services for orphanage children. The results showed that the application of birth certificate ownership in orphanage children was still low so that the Makassar City government through the Department of Population and Civil Registration needs to develop a variety of service innovations to facilitate the community in taking care of birth certificate ownership. Another strategy is to increase human resource capacity and socialization activities.